Recency Effects in the Inferior Parietal Lobe during Verbal Recognition Memory - Buchsbaum, Bradley R.; Ye, Donald; D'Esposito, Mark (Frontiers in Human Neuroscience, 2011)
The most recently encountered information is often most easily remembered in psychological tests of memory. Recent investigations of the neural basis of such “recency effects” have shown that activation in the lateral inferior parietal cortex (LIPC) tracks the recency of a probe item when subjects make recognition memory judgments. A key question regarding recency effects in the LIPC is whether they fundamentally reflect the storage (and strength) of information in memory, or whether such effects are a consequence of task difficulty or an upswing in resting state network activity. Using functional magnetic resonance imaging we show that recency effects in the LIPC are independent of the difficulty of recognition memory decisions, that they are not a by-product of an increase in resting state network activity, and that they appear to dissociate from regions known to be involved in verbal working memory maintenance. We conclude with a discussion of two alternative explanations – the memory strength and “expectancy” hypotheses, respectively – of the parietal lobe recency effect.